A Review of the Synthesis and Photoluminescence Properties of Hybrid ZnO and Carbon Nanomaterials. (3rd October 2016) - Rauwel, Protima; Salumaa, Martin; Aasna, Andres; Galeckas, Augustinas; Rauwel, Erwan
Abstract : Photoluminescent ZnO carbon nanomaterials are an emerging class of nanomaterials with unique optical properties. They each, ZnO and carbon nanomaterials, have an advantage of being nontoxic and environmentally friendly. Their cost-effective production methods along with simple synthesis routes are also of interest. Moreover, ZnO presents photoluminescence emission in the UV and visible region depending on the synthesis routes, shape, size, deep level, and surface defects. When combined with carbon nanomaterials, modification of surface defects in ZnO allows tuning of these photoluminescence properties to produce, for example, white light. Moreover, efficient energy transfer from the ZnO to carbon nanostructures makes them suitable candidates not only in energy harvesting applications but also in biosensors, photodetectors, and low temperature thermal imaging. This work reviews the synthesis and photoluminescence properties of 3 carbon allotropes: carbon quantum or nanodots, graphene, and carbon nanotubes when hybridized with ZnO nanostructures. Various synthesis routes for the hybrid materials with different morphologies of ZnO are presented. Moreover, differences in photoluminescence emission when combining ZnO with each of the three different allotropes are analysed.